TIERRA PÁTRIA BY EDGAR MORIN AND ANNE-BRIGITTE KERN (Isagoge - Journal of Humanities and Social Sciences, 2023)
In Tierra Patria by Edgar Morin and Anne-Brigitte Kern (1993), they reflect on the global responsibility of institutions, communities and governments to facilitate the means, strategies and resources that favour, from a global-planetary perspective, the inclusion of the diversity of knowledge, positions, interpretations and ecosophical ideas in the systems and structures of thought of today's society, For this reason, they address issues such as education, labour, science, philosophy, religion and cultural change, aspects which, when rearticulated in a complex way, can shed new light on the path to follow as humanity to guarantee the existential goal of survival and self-sustainability on Earth.
Keywords: homeland; Complex thinking; Planetary education; Education